Need for Training of Verbal Communication Skills in Hotel Management - Mohanty, Sasmita; Pradhan , Bibhuti B (International Journal of Psychosocial Rehabilitation, 2019)
In terms of communication skills, the pupils in the hospitality industry need to be introduced to actual workplace need. Despite its significance, it needs to be given more serious attention by human resource managers, academics and educators in the hospitality management sector, or by hotel practitioners. It is therefore necessary for both managers and potential employees to decide on what should be instilled in the learners as this would train them for the real reception activities of the hotel, which are, in fact, verbal communication skills. Communication skills requirement and the ability to write and speak effectively in English will be given prominence in this sector. It is therefore of great importance to analyse the language of hospitality that includes the verbal communication skills of hotel management practitioners. Hence this paper discusses the verbal communication abilities of the interns who are the hotel’s future workers. More often than not, the future hotel-post holders have been criticised for missing this expertise despite the good technical knowledge that they may have had during their courses. Technical knowledge is central and therefore cannot be disputed about its significance as this forms the particular basis from which hoteliers work. Nonetheless, technical knowledge alone makes no distinction between the best graduate student and the rest.